Assessing technical and functional features of office buildings and their effects on satisfaction and loyalty - Cheah, Jun Hwa; Ng, Siew Imm; Lee, Chin; Teoh, Kenny Guan Cheng (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
This study assesses the service performance of commercial office buildings in the Golden Triangle Kuala Lumpur (GTKL) and understands how they influence tenant satisfaction and loyalty. Literature suggests that the commercial office building leasing context provides more service components compared to goods, hence, the service performance (SERVPERF) framework was used in this study. Data was collected from 250 tenants of 48 buildings using questionnaires. The Structural Equation Model (SEM) technique was used to test the hypothesis and three significant relationships were found. The result indicated that Building Features, Services and Management performance (BFSM), agglomeration performance and Responsive Customer Orientation (RCO) significantly influenced tenant satisfaction, and subsequently resulted in loyalty. The implications for managers and the theories in this regard are then discussed.